Casamento e cuidados com o cônjuge com demência: Um estudo transcultural Brasil-Portugal - Garcia, C.; Falcão, D.; Pimentel, L. (Psicologia em Estudo, 2019)
This study aimed to analyze the meaning of marriage and care of the spouse from the perspective of Brazilian and Portuguese caregivers of elderly people with Alzheimer Disease (AD). Twelve women participated in the study, being the sample obtained by convenience using the snowball technique. We used a questionnaire and a semi-structured interview, data were analyzed by the Bardin content analysis technique. The results pointed out that although the cultural differences between Brazil and Portugal, some meanings related to marriage and care of the spouse in the context of AD were similar for Brazilian and Portuguese wives. Despite marital changes related to dementia, most wives felt well performing their role of caregiver, perhaps because among other variables, this is a task traditionally and culturally expected to be performed by women of both countries.